BATU NISAN: POLA PENGRAJIN DAN KORELASINYA TERHADAP BUDAYA (Studi Kasus Kampung Gondang Kelurahan Manahan) - Cahyani, Okkie Pritha; Sriiwiyanto, Hery S.J.N; Pratama, Yogi Pasca; Samudro, Bhimo Rizky (Jurnal Ilmu Ekonomi dan Pembangunan, 2015)
This study aims to (1) identify interaction’s pattern of crab’s man of gravestone with market agent (the market agent are crab’s man of gravestone, middleman and consumer), and non market agent (local government and the undertaker).(2) Describe the relation of Java’s culture with business continuity of crab’s man of gravestone in Gondang Village.The unit of analysis in this study is the interaction between crab’s man of gravestone with market agent and non market agent.The data in this study were collected by using several methods, namely unstructured interviews and in-depth interviews and non participant observation. This study use qualitative method with phenomenology approach.The results showed that: (1) there were 5 interaction’s pattern between crab’s man of gravestone with market agents and non market agent (2) the Java’s culture has a big influence toward the business continuity of crab’s man of gravestone.The recommendations idea that given for the crab’s man of gravestone are: (1) The crab’s man of gravestone should make an organization or association of crab’s man of gravestone, in order to have an agreement price directly between the fellow of crab’s man of gravestone. (2) Moreover, the local government should support the business continuity of crab’s man of gravestone directly, and they also should take an action resolutely toward persons who play a negative role in this gravestone’s business. Keywords : crab’s man of gravestone, interaction, market agents and non market agents.JEL Classification: M21, D02, Z12, L19